Polycyclic Aromatic Hydrocarbons in Atmospheric PM2.5 during Winter Haze in Huang-gang, Central China: Characteristics, Sources and Health Risk Assessment - Mingming Shi; Tianpeng Hu; Yao Mao; Cheng Cheng; Weijie Liu; Qian Tian; Zhanle Chen; Xinli Xing; Shihua Qi (Aerosol and Air Quality Research)
Abstract Levels, compositions, sources and health risk of PM2.5-bound PAHs were measured at a regional monitoring site of Huang-gang in the winter of 2018. Samples were collected every morning, afternoon, evening and late night (LN). The average concentrations of PM2.5 and PAHs were 110.4 ± 48.3 µg m−3 and 25.6 ± 12.0 ng m−3, respectively. The concentration of PM2.5 was in the order of evening > morning > afternoon > LN, while PAHs concentration was in the order of evening > LN > morning > afternoon. According to PM2.5 concentration and its changing trend, the haze can be divided into three stages: early (low concentration, January 13–15, EHZ), medium (high concentration, January 16–22, MHZ) and late (concentration decreased rapidly, January 23–24, LHZ). A positive correlation (P < 0.01) was observed between PM2.5 and Σ16PAHs concentration only in MHZ. Besides, PAHs concentration was positively related to NOx concentration, CO concentration and temperature but negatively correlated with RH, independent of O3 concentration. The ratios of OC/EC indicated that the secondary aerosol had a great influence on the formation of haze. Three sources of PAHs including traffic emission, coal combustion and biomass combustion were extracted and quantified, accounting for 54.4%, 13.3% and 32.3% of PAHs, respectively. Potential source contribution function (PSCF) and concentration weighted trajectory (CWT) indicated the transmission of PM2.5 from Wuhan and local pollutant emission were crucial to the formation of haze. BaPeq concentration combined with ILCR values was used to evaluate health risk and the results showed this haze had potential health risk to both adults and children.